Testing color evaporation in photon-photon production of J/psi at CERN LEP II - Eboli, OJP; Gregores, E. M.; Mizukoshi, J. K. (American Physical Soc, 2003)
The DELPHI Collaboration has recently reported the measurement of J/psi production in photon-photon collisions at CERN LEP II. These newly available data provide additional proof of the importance of colored c (c) over bar pairs for the production of charmonium, because these data can be explained only by considering resolved photon processes. We show here that the inclusion of color octet contributions to J/psi production in the framework of the color evaporation model is able to reproduce these data. In particular, the transverse-momentum distribution of the J/psi mesons is well described by this model.